Effect of Inspiratory Muscle Training in the Management of Patients With Asthma: A RANDOMIZED CONTROLLED TRIAL. Issue 3 (May 2018) - Duruturk, Neslihan; Acar, Manolya; Doğrul, Mustafa Ilgaz
Abstract : Purpose: The aim of this study was to investigate the effects of inspiratory muscle training (IMT) on respiratory muscle strength, exercise capacity, dyspnea, fatigue, quality of life, and daily living activities of asthmatic patients. Methods: Thirty-eight asthmatic patients, between 18 and 65 years of age, were enrolled in the study and randomly divided into 2 groups; IMT (n = 20) or control (n = 18). Participants in the IMT group performed 30 breaths using a patient-specific threshold pressure device, twice daily for 6 wk at 50% maximal inspiratory pressure (MIP), in addition to "breathing training" during this period. Participants in the control group performed only the "breathing training" (sham or no threshold pressure device). Outcome measurements, performed before and after the intervention, included pulmonary function test, respiratory muscle strength, 6-min walk test, modified Medical Research Council dyspnea scale, St George's Respiratory Questionnaire, Fatigue Severity Scale, and London Chest Activity of Daily Living scale. Results: Among the outcomes in the study, changes to key variables including MIP ( P < .01); MIP, percent predicted ( P < .01); maximal expiratory pressure (MEP), percent predicted ( P < .01); 6-min walk test walking distance ( P = .001); modified Medical Research Council scale ( P =<.001); Fatigue Severity Scale ( P = .03); St George's Respiratory Questionnaire symptoms ( P = .03); London Chest Activity of Daily Living domestic ( P = .03); and London Chest Activity of Daily Living leisure ( P = .01) were significantly different in favor of IMT versus control. Conclusion: These findings suggest that IMT may be an effective modality to enhance respiratory muscle strength, exercise capacity, quality of life, daily living activities, reduced perception of dyspnea, and fatigue in asthmatic patients. Abstract : We investigated the effects of inspiratory muscle training (IMT) in patients with asthma. Participants (n = 38) were randomized into 2 groups; IMT or control. Results indicated that changes in MIP, MEP, 6MWD, mMRC, fatigue, SGRQ, and LCADL scores were significantly different between IMT and control, indicating that IMT may be an effective intervention in patients with asthma.